Hubungan Kecerdasan Emosional Dengan Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SDN 17 Koto Hilalang - W, Winda; Ilmi, Darul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One way students can be successful in their learning process is by achieving high academic achievement. Daniel Goleman stated that only 20% of a person's success comes from academic intelligence; The other 80% is determined by various characteristics, such as emotional intelligence. The current research begins with the general lack of motivation for each student's learning. Apart from that, there are environmental problems around students, inappropriate learning styles, pressure to achieve, and high expectations to achieve a certain level of achievement. This research tests the relationship between two variables X and Y using correlational research methods and quantitative research techniques. The research population consisted of 55 students, and the total sampling method was used to take samples for each student. Through observation, questionnaires and documentation, data was collected. Linearity and normality tests are part of the data analysis, then the product moment correlation approach is used to assess the hypothesis. After the research data was analyzed and discussed, a sig (2-tailed) value of 0.001 was obtained. And have a significant relationship. Based on research, the results of the hypothesis test carried out have a significance value of 0.001 < 0.05, meaning that Ha is accepted and H0 is rejected. The results of these calculations show that there is a significant relationship between the learning achievement of students in grades III, IV, V and VI at SD Negeri 17 Koto Hilalang and their emotional intelligence.